(untitled) (Journal of Insurance Studies in South Asia, 2025)
Inclusive insurance has become a priority agenda in developing countries like Nepal. This study investigates the inclusive insurance policy for uninsured people using a systematic literature review. The research is based on a review of systematically selected empirical research papers. The Google Scholar search engine was applied using the keywords "social insurance" and "inclusive insurance". All papers that were published from January 2017 to September 2025 have been checked for the study and 21 research papers were selected for this study using the PRISMA framework. The study finds social insurance, microinsurance, public private partnership, solidarity and insurtech model of insurance are effective platforms to expand insurance services to the uninsured people. Adoption of technology-based method, insurance services can be widely expanded and delivered responsive, efficient and inclusive services to the under-served area and people. Inclusive insurance policy is essential to promote collaborative governance with public sectors, market-based instruments, and social institutions to develop a protection framework. Government may promote inclusive insurance environment, enhance capability of insurance institutions and expand the access of insurance services to the uninsured people.